2008
DOI: 10.1007/s12519-008-0039-1
|View full text |Cite
|
Sign up to set email alerts
|

Peak expiratory flow rate of rural school children from Wardha district, Maharashtra in India

Abstract: PEFR is a reliable measurement, which can be used routinely and regularly in rural areas for assessment of airway obstruction and prediction formula derived for use in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0
14

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 5 publications
5
12
0
14
Order By: Relevance
“…Multiple and partial "Bivariate" prediction equation was obtained to predict PEFR from arm span using the formula Y= a+b x The equation is, PEFR (L/min) = -310.06+4.10 X arm span (cms) Values of PEFR observed in the present study are in close agreement with the values reported by Chowgule et al [8], Shamssain[19] and Nairn et al [20]. Lower values are reported by Rivera et al [21], Godfray et al [22], however higher values of PEFR are reported by Veerana et al [23], Dikshit et al [24], Taksande et al [25], Doctor et al [26], Chhabra et al [27]. The differences in values may be due to difference in physical parameter, physical activity, environmental condition, ethnic variation, socio economic status etc [7,[15][16][17].…”
Section: Discussionsupporting
confidence: 92%
“…Multiple and partial "Bivariate" prediction equation was obtained to predict PEFR from arm span using the formula Y= a+b x The equation is, PEFR (L/min) = -310.06+4.10 X arm span (cms) Values of PEFR observed in the present study are in close agreement with the values reported by Chowgule et al [8], Shamssain[19] and Nairn et al [20]. Lower values are reported by Rivera et al [21], Godfray et al [22], however higher values of PEFR are reported by Veerana et al [23], Dikshit et al [24], Taksande et al [25], Doctor et al [26], Chhabra et al [27]. The differences in values may be due to difference in physical parameter, physical activity, environmental condition, ethnic variation, socio economic status etc [7,[15][16][17].…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings were reported by some authors (16)(17).The PEFR (Predicted) values as per the height of the children are lesser than the PEFR(Measured) values. This indicates that height determines the PEFR (Predicted) values but BMI and SFT also has an influence in PEFR (Measured) values.…”
Section: Discussionsupporting
confidence: 90%
“…Similar findings were reported by some authors. [1617] Various studies[511] have shown that the prediction equation based on age and height and those based on age and body surface area did not show significant difference when used to calculate lung function values.…”
Section: Discussionmentioning
confidence: 99%